Access to sport and recreation services for visually impaired and blind people - a case study of the city of Wrocław - Jarosław Maśliński; Patryk Wasilewski; Paweł Piepiora; Kazimierz Witkowski (Nicolaus Copernicus University in Toruń, 2020)
Access to sports services is important for the physical development and functioning of blind and visually impaired people. Access to this type of activity also affects the rehabilitation of people with visual impairment and their daily functioning. Sport activity and participation in various forms of recreation is a very broad concept in physical culture. Understanding the form of physical activities that the visually impaired and blind people prefer can help educators, physical education teachers, and people associated with visually impaired and blind children in planning physical activities. It is important to understand the needs of such people regarding the sports environment and whether they are given active participation in it through infrastructure adapted to the needs of youth with sight disabilities. The aim of the study was to find out the opinions of blind and visually impaired students about the availability of sports and recreation services and equipment in their immediate surroundings. The subject of the study were boys and girls with low vision and blind attending the seventh and eighth grades of primary, secondary (technical and high school) schools at the Special Educational Center for Blind and Visually Impaired Children in Wrocław and among the graduates of that school. The subjects belonged to the age group in the range from 13 to 25 years. The study group included 32 boys and 21 girls. Based on the documentation, the blind group includes students with a significant degree of disability, vision defects. The visually impaired include persons with various moderate and mild eyesight injuries. The research used a survey method of my own authorship, which allowed to know the problem while maintaining anonymity. 26 questions related to min. interests of respondents, access to sports bases, sports sections for the blind and visually impaired. The obtained results showed that it is worth making young people aware of the importance of participation in broadly understood physical culture. Equal opportunities for boys and girls to engage in various types of sports should also be equalized. Not always sports that are preferred by young people are available to them.